The Impact of Public R&D Expenditure on Private R&D Expenditure: The Evidence of Regions of EU Less Developed Countries - Zdražil Pavel (Technická univerzita v Liberci, 2015)
One of the never-ending discussions in economics is connected to government policies and interventions for development in various domains of human society. The topic of science, research and innovation in a global economy belongs to one of them. There are many studies that analysed impacts of public R&D on private R&D among countries but for the regional level they are missing. The aim of this paper is to examine the influence of public R&D expenditure on private R&D expenditure of the regions of EU less developed countries. This aim has been achieved by correlation analysis, and reviewing relations of development of examined volumes. The results have been discussed with some relevant studies in the field of public R&D expenditure impacts on private R&D investment. Based on our findings, we can suggest that there is no common pattern for public R&D influences on private R&D among the regions of EU less developed countries. Furthermore, there are no basic differences between the direct and indirect (i.e. via universities and public institutes) R&D funding for government. We can suggest beyond, it could be even better for government to looking for another effective ways of increasing private R&D, since the changes of private sources which may follow public funding are lesser, then one can expect. At least we can say that public sources are causing crowding out effect of private R&D investment, not the crowding in, which is undesirable; therefore, interventions connected only to increasing funding are simply not part of what regional or central governments may aim at all.
The Impact of Public R&D Expenditure on Private R&D Expenditure: The Evidence of Regions of EU Less Developed Countries
Keywords: R&D expenditure; sectors by performance; EU regions; less developed countries; R&D expenditure; sectors by performance; EU regions; less developed countries